GRICE’S COOPERATIVE PRINCIPLES VIOLATION IN THE COMMUNICATION OF CHILDREN WITH AUTISM - Dian Wahyunianto; Djatmika Djatmika; Dwi Purnanto (Universitas Padjadjaran, 2020)
The involvement of children with autism in social interaction is mostly at a lower level. It is due to the language obstacles faced by children with autism that become the reason why children with autism tend to violate the cooperative principles in communication. This study aims to demonstrate how children with autism violate Grice’s cooperative principles maxims and what causes it. The Grice’s cooperative principles maxims are the focus of this observation and 5 children with autism were the subjects of this study. The research was done in SLBN Surakarta which is the school for exceptional children in Surakarta. By utilizing the observational approach, the data were collected using recording and transcribing technique. Leech’s heuristic pragmatic analysis method was used to analyze the data. The results showed that 67.65% of utterances spoken by the children with autism violated 1 maxim, 20.59% utterances violated 2 maxims and 3 maxims violation was found in 2.94% utterances. 4 maxims violation was also found indicating that there are 8.82% utterances of the children with autism failed to fulfill cooperative principles. Language and social development problems are considered responsible for the violations well as their disability to stay focus are considered the cause of maxim of relevance become the most violated maxim in this study.